Habitat and tree species identity shape aboveground and belowground fungal communities in central European forests - Hofmann, Benjamin; Dreyling, Lukas; Dal Grande, Francesco; Otte, Jürgen; Schmitt, Imke (Frontiers in Microbiology, 2023)
Trees interact with fungi in mutualistic, saprotrophic, and pathogenic relationships. With their extensive aboveground and belowground structures, trees provide diverse habitats for fungi. Thus, tree species identity is an important driver of fungal community composition in forests. Here we investigate how forest habitat (bark surface vs. soil) and tree species identity (deciduous vs. coniferous) affect fungal communities in two Central European forests. We assess differences and interactions between fungal communities associated with bark surfaces and soil, in forest plots dominated either by Fagus sylvatica, Picea abies, or Pinus sylvestris in two study regions in southwestern and northeastern Germany. ITS metabarcoding yielded 3357 fungal amplicon sequence variants (ASVs) in the northern and 6088 in the southern region. Overall, soil communities were 4.7 times more diverse than bark communities. Habitat type explained 48-69% of the variation in alpha diversity, while tree species identity explained >1-3%. NMDS ordinations showed that habitat type and host tree species structured the fungal communities. Overall, few fungal taxa were shared between habitats, or between tree species, but the shared taxa were highly abundant. Network analyses, based on co-occurrence patterns, indicate that aboveground and belowground communities form distinct subnetworks. Our study suggests that habitat (bark versus soil) and tree species identity are important factors structuring fungal communities in temperate European forests. The aboveground (bark-associated) fungal community is currently poorly known, including a high proportion of reads assigned to “unknown Ascomycota” or “unknown Dothideomycetes”. The role of bark as a habitat and reservoir of unique fungal diversity in forests has been underestimated.